A novel MECA3 region in human 3p21.3 harboring putative tumor suppressor genes and oncogenes - Braga, E.; Loginov, W.; Khodyrev, D.; Pronina, I.; Kazubskaya, T.; Bogatyrova, O.; Kashuba, V.I.; Senchenko, V.N.; Klein, G.; Lerman, M.I.; Kisselev, L.L.; Zabarovsky, E.R. (Experimental Oncology, 2011)
Aim of this article is to perform the detailed analysis of 3p (especially 3p21 region) to discover novel potential oncogenes and/or tumor suppressors.